2014
DOI: 10.1037/a0034406
|View full text |Cite
|
Sign up to set email alerts
|

Can we improve cognitive–behavioral therapy for chronic back pain treatment engagement and adherence? A controlled trial of tailored versus standard therapy.

Abstract: Participants in this study evidenced a high degree of participation and adherence, but treatment tailored to take into account participant preferences, and that employed motivational enhancement strategies, failed to increase treatment participation over and above SCBT for chronic back pain. Evidence that participation and adherence were associated with positive outcomes supports continued clinical and research efforts focusing on these therapeutic processes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
80
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 78 publications
(87 citation statements)
references
References 26 publications
6
80
0
1
Order By: Relevance
“…In comparison with other studies, adherence for CBT for chronic back pain has shown to be associated with treatment gains in a variety of outcome measures including accomplishment of daily goals. 142 Attendance was good, with 23 participants (88%) attending at least half of the sessions.…”
Section: Best Usual Carementioning
confidence: 99%
“…In comparison with other studies, adherence for CBT for chronic back pain has shown to be associated with treatment gains in a variety of outcome measures including accomplishment of daily goals. 142 Attendance was good, with 23 participants (88%) attending at least half of the sessions.…”
Section: Best Usual Carementioning
confidence: 99%
“…Various studies examining CBT as a treatment modality for chronic pain have demonstrated reductions in patient pain severity, disability, distress, and healthcare use in relation to their pain experience (Kerns et al 2013). There are some very close similarities between the CBT modalities when targeting pain, and each aims for psychological flexibility and adaptive cognitive and behavioral pursuits.…”
Section: Best Treatment Of Catastrophizingmentioning
confidence: 98%
“…Impacting the efficacy of self-management and self-efficacy focused interventions are motivational factors often cited in Prochaska's stages of change model and Motivational Interviewing. A patient's readiness to adopt a self-management approach impacts the adherence and dropout rates of such interventions (Kerns et al 2013). The self-management and self-efficacy approach is not uniform in effectiveness however.…”
Section: Self-management and Self-efficacymentioning
confidence: 99%
“…This could be particularly powerful when combined with deliberate intervention tailoring. For example, allowing individuals to pick from a menu of self-management strategies may be as effective as the clinician picking which strategies are used, (46) but has the potential to be more feasible and acceptable to patients. Further investigation into such interventions among HIV-infected individuals with chronic pain is needed.…”
Section: Discussionmentioning
confidence: 99%